THE ROLE OF AGE IN THE DEVELOPMENT OF PRAGMATIC COMPETENCE IN SECOND LANGUAGE ACQUISITION: A THEORETICAL REVIEW OF CHILDREN AND ADULT LEARNERS - Jabborova Dilnoza Jobir kizi (International Journal of Literature and Language Studies, 2026)
Pragmatic competence, which is considered one of the important components of Second Language Acquisition (SLA) process, allows learners to use language units appropriately in various social and cultural situations. In recent years, studies conducted in the field of second language acquisition have centered attention on factors that influence the development of pragmatic competence, especially the age factor. This theoretical review article is aimed at analysing the role of age in the development of pragmatic competence in children and adult learners. In this article, existing literature on pragmatic competence, communicative competence, interlanguage pragmatics and age-related theoretical approaches will be reviewed. Also, based on Critical Period Hypothesis, cognitive development theories and researches about pragmatic development, differences between children and adults will be analysed. Literature review shows that children, because of a long-term exposure to naturalistic language environment and social interactions, might have an advantage in acquiring pragmatic norms more naturally. In addition, adults can efficiently develop pragmatic competence with the help of advanced metalinguistic knowledge, analytical thinking and conscious learning strategies.